Jørgen Leth - Film Portraits, Disc 2 - Leth, Jorgen; Brüel, Dirk; Holmberg, Dan (Danish Film Institute, 2008)
In Leth's trademark tableaux "Klaus Rifbjerg" (1974), renowned novelist, Rifbjerg, reflects on a variety of subjects, among them the relationship between gravity and pretence, hatred of art, political art, the absurdity of life and the basic conditions of existence. We have to hone our ears and brains to get every point the poet makes in the stories he tells in "I'm Alive. Søren Ulrik Thomsen: A Danish Poet" (1999). Meanwhile Leth's black and white images have a poetry and beauty of their own that curl around Thomsen's words and take us in other directions. Poetry is likewise at the heart of "Danish Literature" (1989), spanning the spectrum from hymn writer H.A. Brorson to punk poet Michael Strunge. Lavish, almost dreamlike shots of Danish countryside are intercut between poems read by professional readers or the poets themselves. [www.dfi.dk]
Keywords: DVD-Video